Massive Endometroid Ovarian Carcinoma and Synchronous Uterine Malignancy - Shazia Sultana; Rubina Hussain; Wasiya Irfan (ziauddin University, 2024)
The diagnosis of ovarian carcinoma is a challenging task especially when women usually present vague symptoms like abdominal distension and pain. The aim of this paper is to report a case of synchronous ovarian malignancy in a young patient. A 36 year old unmarried female presented with a huge right ovarian cystic mass occupying the whole abdomen, breathlessness, jaundice and urinary retention. She underwent laparotomy for surgical removal of the mass and during the surgical procedure a frozen section was performed that showed malignancy. Total abdominal hysterectomy and bilateral salpingo ophorectomy was thereafter performed on her. Final histopathological report of the mass revealed well differentiated endometroid ovarian cancer and endometroid endometrial cancer. Synchronous endometroid tumors are generally present in young patients; these tumors tend to be of low grade malignancy. Prognosis of endometroid carcinoma is relatively better than other histological types. KEY WORDS: Endometroid Tumour, Total Abdominal Hysterectomy, Bilateral Salphingo-Oophorectomy, Laparotomy.